Oxolipidomics profile in major depressive disorder: Comparing remitters and non-remitters to repetitive transcranial magnetic stimulation treatment. - Hannah Stirton; Benjamin P Meek; Andrea L Edel; Zahra Solati; Arun Surendran; Harold Aukema; Mandana Modirrousta; Amir Ravandi (PLoS ONE, 2021)
Background Repetitive Transcranial Magnetic Stimulation [rTMS] is increasingly being used to treat Major Depressive Disorder [MDD]. Given that not all patients respond to rTMS, it would be clinically useful to have reliable biomarkers that predict treatment response. Oxidized phosphatidylcholine [OxPC] and some oxylipins are important plasma biomarkers of oxidative stress and inflammation. Not only is depression associated with oxidative stress, but rTMS has been shown to have anti-oxidative effects. Objectives To investigate whether plasma oxolipidomics profiles could predict treatment response in patients with treatment resistant MDD. Methods Fourty-eight patients undergoing rTMS treatment for MDD were recruited along with nine healthy control subjects. Plasma OxPCs and oxylipins were extracted and analyzed through high performance liquid chromatography coupled with mass spectrometry. Patients with a Hamilton Depression Rating Scale score [Ham-D] ≤7 post-treatment were defined as having entered remission. Results Fifty-seven OxPC and 32 oxylipin species were identified in our subjects. MDD patients who entered remission following rTMS had significantly higher pre-rTMS levels of total and fragmented OxPCs compared to non-remitters and controls [one-way ANOVA, p<0.05]. However, no significant changes in OxPC levels were found as a result of rTMS, regardless of treatment response [p>0.05]. No differences in plasma oxylipins were found between remitters and non-remitters at baseline. Conclusion Certain categories of OxPCs may be useful predictive biomarkers for response to rTMS treatment in MDD. Given that elevated oxidized lipids may indicate higher levels of oxidative stress and inflammation in the brain, patients with this phenotype of depression may be more receptive to rTMS treatment.